Economic Nationalism and Its Vitality in India - Dinh Thi Phuong Thao, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Nationalism is a close link of three components, which are economic, political, and social nationalism. Although economic nationalism focuses on encouraging domestic consumption, adopting protection policies, and restricting imports, the final concerns of the nation are still territory and power. India, which has many competitive advantages but also faces a lot of obstacles on the development path, maintains economic nationalism in many different forms from M. Gandhi to N. Modi’s time. In the era of globalization and modernization, economic nationalism has remained persistent and has become an ideological system to help build a sustainable and stable economy. The article focuses on three main contents: (i) Overview of economic nationalism, (ii) economic nationalism in India and as it has grown in the past, and (iii) economic nationalism in India as it stands today and in the future.Received 25th September 2020; Revised 2nd January 2021; Accepted 20th February 2021